2020
DOI: 10.1186/s12935-020-01226-7
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights into eukaryotic translation initiation factors 5A1 and 5A2 and their roles in human health and disease

Abstract: The eukaryotic translation initiation factor 5A1 (eIF5A1) and its homolog eIF5A2 are the only two human proteins containing the unique post-translational modification-hypusination, which is essential for the function of these two proteins. eIF5A1 was initially identified as a translation initiation factor by promoting the first peptide bond formation of protein during translation; however, recent results suggest that eIF5A1 also functions as a translation elongation factor. It has been shown that eIF5A1 is imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 123 publications
0
23
0
2
Order By: Relevance
“…eIF5A1 is abundantly expressed in most cells and functions as a translation elongation factor. It was also shown that eIF5A1 is implicated in certain human diseases, including diabetes, several human cancer types, viral infections and diseases of the nervous system ( 12 ). Meanwhile, eIF5A2 is overexpressed in numerous cancers, expressed few normal tissues, is a candidate oncogene and plays an important role in the development and progression of cancers ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…eIF5A1 is abundantly expressed in most cells and functions as a translation elongation factor. It was also shown that eIF5A1 is implicated in certain human diseases, including diabetes, several human cancer types, viral infections and diseases of the nervous system ( 12 ). Meanwhile, eIF5A2 is overexpressed in numerous cancers, expressed few normal tissues, is a candidate oncogene and plays an important role in the development and progression of cancers ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…EIF5A is important both for translational elongation, particularly at ribosome stalling sites, and for termination 38 . EIF5A2 may also function in mRNA decay in response to stress 39 , and both factors have been implicated in human diseases such as cancer 40 .…”
mentioning
confidence: 99%
“…EIF5A is important both for translational elongation, particularly at ribosome stalling sites, and for termination ( 43 ). EIF5A2 may also function in mRNA decay in response to stress ( 44 ), and both factors have been implicated in human diseases such as cancer ( 45 ).…”
Section: Resultsmentioning
confidence: 99%